Pentingnya Bersyukur sebagai Self Concern terhadap Diri Sendiri: Studi Takhrij dan Syarah Hadis - Fadhil Rahman Utama (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the Hadith about the importance of gratitude towards oneself. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the importance of being grateful to oneself in Imam Ahmad's narration No. 20459. The results and discussion of this research show that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Imam Ahmad No. 20459 is relevant to be used as a spirit of gratitude towards oneself.